Research on coaching behavior of football club - Shiozawa, T.; Maeda, H. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In sports coaching, it is significant for a coach to acquire suitable knowledge and skills. In the past researches on coaches in the football club, the expectation from the participant side was apparent, such as players or parents` expectation. However, expectation from an organization was ambiguous. This study clarifies the expectation of the coaching behavior by the football clubs` principals. A leadership PM theory (Misumi, 1966) is used for a framework in this Research. Methods In this study coaching behavior was divided into two functions, the performance function and the maintenance function, the based on PM leadership theory. And, two investigations were conducted. One is an investigation about a principals, the other is about a coach. The semi-structured interviews were conducted with 6 principals who work in the football club. The informants were asked about the expectation of the coaching behavior and the measures for the improvement in coaching behavior. And, 16 coaches responded to the questionnaire on their own coaching behavior. Results & Discussion The results are summarized as follows; 1) The characteristic of.. coaching behavior include "demonstration," "planning," "age-appropriate coaching," "develop discipline," "communicate with each player," "observe players carefully" 2) Principals expect P function and M function equally to a coach in five clubs. 3) There is a difference by the existence of training workshop about M function. 4) Coach conscious P function and M function equally. Conclusion The results showed principals expect P function and M function equally, but training workshop about M function less than P function. It is suggested that it is required to improve the environment where a club can be given workshop. And, it is also important cooperation with sports associations or public administration.